The language of the epos is the basis for the formation of the national consciousness of the youth (Eurasian Journal of Philology Science and Education, 2023)
The article reveals the source of the national culture of all peoples  of the world, the golden fund of historical memory, national worldview – folklore, particular , the influence of the language of the epic heritage on the formation of the national self – awareness of youth. Folklore is not only the world of the past , but also the art that lives in the country today. We can say that with the help of such linguistic mechanisms, it helps prevent negative social changes in the behavior of children and young people in modern society.Today, in the period of intensive development of information delivery, human capabilities are immediately expanding, and accordingly, it is noticeable that the interest in the problem of personality research is growing significantly. At the same time, it will be very important to know the mechanism of transmission and functioning of language units in the human mind, to recognize its national character.The result was in epic songs such as «Love for the Fatherland», «Defense of the Motherland», «Respect for family and friends», and other traditions and laws of the steppe.As a result of the research, it can be said that the need to consider the nature of the language in connection with the history of the nation, epic songs, one of the rich oral literature heritages, is shown by the new researches of Kazakh linguistics based on national knowledge.